PENGARUH PEMAHAMAN UNSUR-UNSUR MUSIK TERHADAP KEMAMPUAN ANALISIS MUSIK SISWA KELAS XI DALAM PEMBELAJARAN SENI MUSIK - Maria Abi; Paskalis R Langgu; Gregorius V Ukat (Program Studi Pendidikan Musik, 2026)
This study aims to determine the effect of understanding musical elements on the music analysis skills of 11th grade students in Music Arts classes at St. Arnoldus Jansen High School. Understanding musical elements, such as melody, rhythm, harmony, tempo, dynamics, and song form, is an important foundation for developing musical appreciation and analysis skills. The method used is a quantitative method with a correlational approach. Data collection was conducted through questionnaires to measure the level of understanding of musical elements and tests to assess students' musical analysis skills. The research instruments were tested for validity and reliability before use. Data analysis was performed through normality, homogeneity, Pearson correlation, and simple regression tests using SPSS version 25. The results show that the data are normally distributed and homogeneous, thus meeting the requirements for parametric analysis. The correlation test yielded a value of r = 0.305 with Sig. = 0.070, while the regression test yielded a value of F = 3.494 and Sig. = 0.070. Both results indicate that there is a positive but insignificant relationship between understanding musical elements and musical analysis skills. Thus, understanding musical concepts does not yet have a significant effect on students' musical analysis skills, which may be influenced by other factors such as practical experience and interest in learning music.